Advances in librarianship. Vol. 30 - Nitecki, Danuta A.; Abels, Eileen G. (Emerald, 2006)
The 30th volume of Advances in Librarianship acknowledges changes in the profession over three and a half decades, while continuing a tradition of identifying new trends and innovations. The contributing authors were invited especially to celebrate the history of the past thirty-six years by reflecting, as appropriate, on advances made in their topic since the first volume of the series was published in 1970. The twelve chapters in this volume can be loosely grouped into four sections reflecting basic themes in librarianship: tracing issues in communication: relevance and freedom of expression; focusing on library services and resources; tailoring services to different user groups; and educating the profession for the future. Together these offer a milestone in the retrospective view of advances in librarianship. It examines changes and developments over the past three decades. The four sections are: Tracing issues in communication: Relevance and Freedom of Expression, Focusing on library services and resources, Tailoring services to different user groups, and Educating the profession for the future.
Includes index.
Keywords: Library science.; Information science.; elektronické knihy; electronic books